2021
DOI: 10.1038/s41467-021-24254-x
|View full text |Cite
|
Sign up to set email alerts
|

Grain-boundary-rich polycrystalline monolayer WS2 film for attomolar-level Hg2+ sensors

Abstract: Emerging two-dimensional (2D) layered materials have been attracting great attention as sensing materials for next-generation high-performance biological and chemical sensors. The sensor performance of 2D materials is strongly dependent on the structural defects as indispensable active sites for analyte adsorption. However, controllable defect engineering in 2D materials is still challenging. In the present work, we propose exploitation of controllably grown polycrystalline films of 2D layered materials with h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 52 publications
0
30
0
Order By: Relevance
“…TMD monolayers with direct band gaps exhibit strong photoluminescence (PL) emission in the visible and nearinfrared ranges and are widely used in optoelectronic devices such as light emitters and photodetectors. Kim et al 35 observed strong PL emission from the edges and GBs of WS 2 monolayers (Figure 9a) that is associated with trion and biexciton formation. The PL strength shows different degrees of attenuation in different areas.…”
Section: Optical Propertiesmentioning
confidence: 99%
See 3 more Smart Citations
“…TMD monolayers with direct band gaps exhibit strong photoluminescence (PL) emission in the visible and nearinfrared ranges and are widely used in optoelectronic devices such as light emitters and photodetectors. Kim et al 35 observed strong PL emission from the edges and GBs of WS 2 monolayers (Figure 9a) that is associated with trion and biexciton formation. The PL strength shows different degrees of attenuation in different areas.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…The device showed gate-tunable heterosynaptic functionality with a wide tunability of individual states and switching ratios, effectively functioning like neurons in the brain. In addition, it also shows potential in other functional electronic devices, including sensors and photonic moderators . For example, Liu et al developed a high-GB-density WS 2 film for ultrasensitive Hg 2+ sensors.…”
Section: Properties Of Gbsmentioning
confidence: 99%
See 2 more Smart Citations
“…The detection strategy part could be overcome by using new nanomaterials as the substrate material to improve the primary signal [ 121 ]. The second antibody could be used to amplify the signal of the biosensor.…”
Section: Summary and Prospectmentioning
confidence: 99%